Is innovation a risky business? A comparative analysis in high-tech and traditional industries in Poland - Tomasz Nawrocki; Izabela Jonek-Kowalska (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
A high level of innovativeness and technology complexity is most often associated with a faster and more dynamic pace of economic development. In turn, it enables enterprises to achieve better financial results and strengthen their competitive advantage. Despite these potential benefits, in practice, innovation is also associated with the need to take up new challenges, which may be accompanied by a higher risk. The main goal of the research is a comparative analysis of the relationship between innovation and the risk of running a business in traditional and high-tech industries exemplified by the Polish economy. The authors assess the risk in 44 enterprises in the years 2010-2020 based on the proprietary evaluation model that uses the variation of financial parameters associated with innovativeness. The obtained results indicate a higher level of risk in the high-tech group with more complex and modern technologies, in particular in the pharmaceutical and computer games sectors. In the group of traditional enterprises, the risk in the analysed sectors is more diversified, and it is much higher in manufacturing enterprises than in services and trade. The empirical and quite extensive nature of the research allows for a practical assessment of the direction and strength of the relationship between innovation, risk and technology complexity.
Keywords: 650; innovativeness; innovativeness in high-tech and traditional industries; risk in innovative activity; technology and its complexity; the impact of innovativeness on risk